Climate Change Alters Temperate Forest Canopies and Indirectly Reshapes Arthropod Communities - Sallé, Aurélien; Cours, Jérémy; Le Souchu, Elodie; Lopez-Vaamonde, Carlos; Pincebourde, Sylvain; Bouget, Christophe (Frontiers in Forests and Global Change, 2021)
Global change challenges the adaptive potential of forests. Large-scale alterations of forest canopies have been reported across Europe, and further modifications are expected in response to the predicted changes in drought and windstorm regimes. Since forest canopies are dynamic interfaces between atmosphere and land surface, communities of canopy-dwelling insects are at the forefront of major changes in response to both direct and indirect effects of climate change. First, we briefly introduce the factors shaping arthropod communities in the canopy of temperate forests. Second, we cover the significant impacts of a forest decline on canopy structure and functioning, and more specifically its contrasted effects on insect microhabitats, trophic resources and forest microclimates. Deleterious effects may be expected for several guilds of leaf-dwelling insects. Nonetheless, a forest decline could also lead to transient or long-lasting resource pulses for other canopy-dwelling guilds, especially saproxylic species depending on deadwood substrates and tree-related microhabitats. The novel microclimates may also become more favorable for some particular groups of insects. We pinpoint current knowledge gaps and the technological locks that should be undone to improve our understanding of the canopy biotope and biodiversity in temperate forests. We highlight the need for integrative approaches to reveal the mechanisms at play. We call for cross-scale studies and long-term collaborative research efforts, involving different disciplines such as community and disturbance ecology, plant and insect ecophysiology, and thermal ecology, to better anticipate ongoing functional and conservation issues in temperate forest ecosystems.